Work and Health: A Situational Analysis of Factory Workers: Exploring the Challenges Faced by Factory Workers in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
One-third of India's population (nearly a billion people) is working class. Around 5000 of themore than 2 million registered factories are categorized as chemical industry, with more than 5 millionworkers. The human body may be adversely affected by a broad variety of conditions during work,including inappropriate working practices, environmental dangers, and hazardous chemicals. Emergingoccupational health hazards are a consequence of globalization and fast industrial expansion over thelast several years. As a result, there is a strong desire to expose the working conditions of factoryworkers. Workers at an ordnance manufacturing encounter a number of challenges, including theirsocioeconomic situation, working circumstances, and health. This research investigates how theseworkers might overcome these challenges.